Economic issues of treating patients with stage 5D chronic kidney disease by dialysis methods of renal replacement therapy in Ukraine: a single-center study - Shymova А.Yu.; Shifris, I.M.; Krasiuk Е.K. (KIDNEYS, 2024)
Background. The aim of the work was to determine the cost of treating patients with stage 5D chronic kidney disease (CKD) by dialysis methods of renal replacement therapy (RRT) in 2023 based on the analysis of the costs of using hemodialysis (HD) and peritoneal dialysis (PD) in one medical institution. Materials and methods. An open single-center study was conducted at the Кyiv City Center of Nephrology and Dialysis. During 2023, 779 patients with stage 5D chronic kidney disease received renal replacement therapy by dialysis methods in this institution. Among them, 718 participants were treated by hemodialysis and 61 patients by peritoneal dialysis (36 by continuous ambulatory peritoneal dialysis (CAPD) and 25 by automated peritoneal dialysis (APD)). Direct medical and non-medical costs were included in the calculation of the cost of treating chronic kidney disease patients using both dialysis methods. The estimate of the cost of treatment for one patient during the year was calculated according to the formula: when using hemodialysis/hemodiafiltration (HDF) method — the cost of 1 session × 156 sessions, in case of CAPD/APD — the cost of 1 treatment day × 365 days. Results. The analysis of the costs for the treatment of patients with stage 5D CKD allowed us to state that the average cost of one HD/HDF session in 2023 was 3,626.20 UAH, one day of CAPD and APD treatment was 1,539.78 and 1,829.12 UAH, respectively. The average cost of treatment of one patient by HD/HDF method during 2023 was 565,687.20 UAH, CAPD — 562,019.70 UAH, APD — 667,628.80 UAH. In the structure of the cost of treatment, regardless of the modality of RRT, the most expensive component is the cost of consumables. State reimbursement under the Program of Medical Guarantees in 2023 for the treatment of one patient with stage 5D CKD during the year was 385,788 UAH when using GD/GDF, 412,085 UAH for CAPD, 662,110 UAH for APD. That is, based on the data we received, the Program of Medical Guarantees covers only 68.2 % of the costs of medical institution for the treatment with HD/HDF, 73.3 % for the treatment with CAPD and almost 100 % for the treatment with APD. Conclusions. The real cost of treating patients with stage 5D CKD using dialysis methods of RRT is higher than the rate of state reimbursement. The Program of Medical Guarantees doesn’t fully cover the costs of medical institutions for the treatment of patients with stage 5D CKD using RRT methods. CAPD has indisputable advantages in terms of both medical and economic benefit. In addition, the advantage of using CAPD over other dialysis modalities during the war is the absence of dependence on water and electricity supply, the number and workload of medical personnel, the need for patients to constantly visit the dialysis center.